Cds1 Controls the Release of Cdc14-like Phosphatase Flp1 from the Nucleolus to Drive Full Activation of the Checkpoint Response to Replication Stress in Fission Yeast - Díaz-Cuervo, Helena (The American Society for Cell Biology, 2008)
The Cdc14p-like phosphatase Flp1p (also known as Clp1p) is regulated by cell cycle-dependent changes in its subcellular localization. Flp1p is restricted to the nucleolus and spindle pole body until prophase, when it is dispersed throughout the nucleus, mitotic spindle, and medial ring. Once released, Flp1p antagonizes Cdc2p/cyclin activity by reverting Cdc2p-phosphorylation sites on Cdc25p. On replication stress, ataxia-telangiectasia mutated/ATM/Rad3-related kinase Rad3p activates Cds1p, which phosphorylates key proteins ensuring the stability of stalled DNA replication forks. Here, we show that replication stress induces changes in the subcellular localization of Flp1p in a checkpoint-dependent manner. Active Cds1p checkpoint kinase is required to release Flp1p into the nucleus. Consistently, a Flp1p mutant (flp1-9A) lacking all potential Cds1p phosphorylation sites fails to relocate in response to replication blocks and, similarly to cells lacking flp1 (Δflp1), presents defects in checkpoint response to replication stress. Δflp1 cells accumulate reduced levels of a less active Cds1p kinase in hydroxyurea (HU), indicating that nuclear Flp1p regulates Cds1p full activation. Consistently, Δflp1 and flp1-9A have an increased percentage of Rad22p-recombination foci during HU treatment. Together, our data show that by releasing Flp1p into the nucleus Cds1p checkpoint kinase modulates its own full activation during replication stress.